2018
DOI: 10.12681/jhvms.15642
|View full text |Cite
|
Sign up to set email alerts
|

Crude glycerol negatively affects rabbit spermatozoa motility in vitro

Abstract: In recent years the conventional diet for farmed animals has been increasingly substituted by alternative energy sources such as crude glycerol. There is an urgent need for investigation of the impact of crude glycerol on the male reproductive tract. Rabbit semen was cultured in a TRIS/NaCl-based medium containing 0% (control), 5%, 10%, 15% and 20% crude glycerol. Sperm kinetic characteristics were assessed immediately and 30 min, 60 min, 120 min and 180 min upon treatment by computer assisted analyzer. In gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The results showed that 5% glycerol slightly reduced total motility, while 10%, 15%, and 20% glycerol significantly decreased total overall motility at all time points. Similarly, increasing the concentration of DMSO improved sperm motility after thawing, but it caused acrosome damage to a large extent and reduced pregnancy rates with increasing concentrations (Paal et al, 2016). Overall, the study confirms that an optimal concentration of glycerol or DMSO can improve rabbit sperm quality and that the findings are consistent with previous research.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that 5% glycerol slightly reduced total motility, while 10%, 15%, and 20% glycerol significantly decreased total overall motility at all time points. Similarly, increasing the concentration of DMSO improved sperm motility after thawing, but it caused acrosome damage to a large extent and reduced pregnancy rates with increasing concentrations (Paal et al, 2016). Overall, the study confirms that an optimal concentration of glycerol or DMSO can improve rabbit sperm quality and that the findings are consistent with previous research.…”
Section: Discussionmentioning
confidence: 99%